Validity and Reliability of Parenting Stress Construct among Mothers of Children with Autistic Spectrum Disorder - Daulay, Nurussakinah; Ramdhani, Neila; Hadjam, Noor Rochman (Faculty of Psychology, Universitas Gadjah Mada, 2020)
Parents of children with developmental disorders are prone to experiencing parenting stress. This study aimed to examine the validity and reliability of the parenting stress construct. A total of 125 mothers of children with autistic spectrum disorder were involved in this study. The results showed that parenting stress consists of three domains: parent, child, and parent-child interaction. This was proven through a validity test using exploratory and confirmatory analysis. The exploratory analysis indicated that the Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was 0.716, meeting the requirement value of above 0.5. Additionally, Bartlett's test of sphericity was significant (p <0.05). Based on the confirmatory analysis, the model was classified as fit with the index: X² (50, N = 125) = 71.98, p = 0.023, RMSEA = 0.060, GFI = 0.91; IFI = 0.94; CFI = 0.94; and RMSEA = 0.077; convergent validity values (λ> 0.5; and AVE values> 0.5); construct reliability values (CR = 0.846). Analysis of psychometric properties of parenting stress met the assumptions of good construct validity and reliability.